THE EFFECT OF USING JOLLY PHONICS ON JORDANIAN FIRST GRADE PUPILS' READING - Abeer Nasrawi; Dina Al-Jamal (Informascope, 2017)
Jolly Phonics is so much fun and favored by pupils by means of being superior to any conventional method. This study investigated the effect of Jolly Phonics strategy on Jordanian first grade pupils' reading. The study followed a quasi- experimental research design. The participants of the study consisted of 58 first grade pupils purposefully chosen from a school in Irbid city, Jordan. Based on the results of a reading pre- tests, two groups are assigned: an experimental group which consists of 29 pupils taught by using the Jolly Phonics strategy under study for five weeks, and a control group of 29 pupils taught by using the Conventional strategy suggested by Action Pack 1 Teacher's Guide, during the first semester of the academic year 2015-2016. In the current study, four instruments were used: a reading test, Jolly Phonics strategy worksheets, and Jolly Phonics songs with the Action Way. The findings of the study reported positive statistical effect of the strategy in focus.